Human capital of the region as a factor of growth of its efficiency (on the example of Yaroslavl region) - M. A. Snurnitsyna (Модернизация, инновация, развитие, 2019)
Purpose: the main purpose of this article is to study human capital as a factor of its efficiency growth. To achieve this goal in the article it is necessary to solve the following tasks: to study the theory of human capital; to study the world and domestic practice of the effectiveness of the territories (subjects of the Russian Federation); analyze human capital and efficiency of the Yaroslavl region.Methods: this article is based on the analysis of statistical data on human capital in the regions of the Russian Federation, the analysis of statistical data on human capital in the countries of the world and the method of benchmarking (comparison of data on the effectiveness of the countries of the world and the human capital of the regions).Results: the most important direction of development of the regional economy is the development of human capital, knowledge management and digital economy. The success of solving these problems is possible when synchronizing at the micro, meso- and macro-levels. Macro- and meso-level strategy sets the vector of micro-level development, in turn, the micro-level is an indicator of the strategy implementation.Conclusions and Relevance: the materials presented in the article show the special role of human capital in the competitiveness of the territory. The research carried out in this article is the development of scientific ideas about modern methods of assessing the effectiveness of territories (subjects of the Russian Federation) in terms of human capital. The practical application of the results of the article will allow to assess the human capital of the regions, to compare the human capital of effective regions and outsiders, to identify weak and strong areas of the territory through which it is possible to influence the efficiency of the region.